The influence of spokesperson achievement on consumer goal pursuit : a dual-mechanism perspective - Kuo, Tzu-Yin (Nanyang Technological University, 2018)
While highly successful spokespersons are ubiquitous in the marketplace, ordinary ones with lower domain achievements are increasingly being featured in sports and fitness-related marketing communication campaigns. This research involves exploring this emerging trend by examining how the spokesperson’s level of achievement influences consumers’ motivation to pursue a goal in the same domain.